The Association Between Intimate Partner Violence and Signs of Depression During Pregnancy in Kilimanjaro Region, Northern Tanzania. Issue 23 (December 2020) - Manongi, Rachel; Rogathi, Jane; Sigalla, Geofrey; Mushi, Declare; Rasch, Vibeke; Gammeltoft, Tine; Meyrowitsch, Dan W.
Intimate partner violence (IPV) against pregnant women is common with severe health consequences to women and their babies. The aim of the present study is to measure the association between IPV and signs of depression among pregnant women attending antenatal care in a semi-urban setting in northern Tanzania. A cross-sectional study was conducted from March 1, 2014, to May 30, 2015, among pregnant women attending routine antenatal care in Moshi Municipality, Tanzania. During their third trimester, self-reported exposure to IPV was assessed using a validated structured questionnaire adopted from the World Health Organization's (WHO) Multi-Country Study on Women's Health and Domestic Violence. Signs of depression were assessed using Edinburg Postpartum Depression Scale. A total of 1, 116 pregnant women were included in the analysis. A total number of 433 (38.8%) reported to be exposed to at least one type of violence during their pregnancy, and 128 (11.5%) presented with signs of depression. The most common type of violence experienced was emotional violence (30.7%), followed by sexual violence (19.0%) and physical violence (10.0%). Exposure to at least one type of violence was the strongest predictor for depression (adjusted odds ratio [AOR] = 5.06; 95% confidence interval [CI] = [3.25, 7.86]), followed by women who reported their primary source of emotional support was individuals not related to their family as compared with support obtained from their male partner/husband (AOR = 2.25; 95% CI = [1.26, 4.02]). Positive HIV/AIDS status (AOR = 2.27; 95% CI = [1.01, 5.14]) and previous history of depression (AOR = 1.62; 95% CI = [1.00, 2.64]). After adjusting for other predictors and types of violence, physical violence was the strongest predictor for signs of depression (AOR = 4.42; 95% CI = [2.65, 7.37]). Signs of depression were commonly observed among pregnant women and strongly associated with exposure to any type of IPV. The present findings indicate an urgent need for screening depression and IPV to mitigate the adverse health outcomes related to both IPV and depression during pregnancy.